Dominância fiscal e os seus impactos na política monetária : uma avaliação para a economia brasileira (2000 -2015) - Souza, João Batista da Luz de (2016)
The objective of this study is to analyze the interaction between fiscal and monetary policies in the Brazilian economy - specifically the relationship between public debt and default risks as potential determinants of the existence of macroeconomic imbalances, which are reflected in the price level. In economic literature, the fiscal dominance occurred when there was the concern of the tax authorities in maintaining acceptable levels in the public debt in proportion to GDP. Another aspect considers a specific type of fiscal dominance manifested from an exchange rate depreciation when the central bank seeks to operationalize the interest rate to curb inflation - this would occur before some specific conditions. The empirical analysis was performed from the Vector Error Correction Model (VEC), using monthly data for the period from December 2001 to June 2015. The model suggests that fiscal policy from the public debt plays an important role in determining the rate of inflation. The results indicate that the Brazilian economy is under fiscal dominance consequently the central bank loses its main monetary policy instrument - the interest rate.